New development areas (NDAS) in rural Hong Kong : whose spatial justice and whose right to the city? - Ng, Mee Kam (AESOP, 2015)
Justice is a prerequisite for civil order (Rasmussen, 1999). To many Hong Kongers, the return to Chinese rule since 1997 has seen the further bias of the Governments policies towards t recent controversial plan that has triggered multiple protesting acts is to bull-doze farms and nonindigenous farmers in rural New Development Areas (NDAs) to make way for housing product ultra-expensive commodity fueled by growing demand from local residents and Chinese investors. If justice means giving people what they deserve (Sandel, 2009, p.7), then the ca thought. Legally, justice is done when non-indigenous farmers who are also squatters, are cleared to make way for housing construction. Socio-economically, the move is to liberate the land value and provide homes for hundreds of thousands of urbanites. However, from a geographical equity point of view, these multi-generation farmers have played a significant role in securing local farm produces to the city. So whose right to the city should be protected: Farmers rights to their farming pr rights to be displaced? Or the claim rights of many urbanites to reasonable housing? Detailed examination of the evolution of the NDA plans reveals the importance of the right to voice out differences to prevent the complete transformation of spaces saturated with use values to exchange values. Nevertheless, the NDA plans can still be seen as a smokescreen to fatten the pockets of big developers who have accumulated huge land banks in the NDAs.
Book of proceedings: Annual AESOP Congress, Definite Space – Fuzzy Responsibility, Prague, 13-16th July, 2015
Keywords: spatial justice; the right to the city; Hong Kong